Novel Delivery of Meaningful EMS and Disaster Medicine Content to Residents and Medical Students. Issue Volume 34:Issue s1(2019) (May 2019) - Flax, Lindsay; Liu, E. Liang; Miller, Brian; Morshedi, Brandon; Fowler, Raymond L.; Swienton, Raymond E.; Mugele, Josh; Klein, Kelly
Abstract : Introduction: Residency education delivery in the United States has migrated from conventional lectures to alternative educational models that include mini-lectures, small group, and learner lead discussions. As training programs struggle with mandated hours of content, prehospital (EMS) and disaster medicine are given limited focus. While the need for prehospital and disaster medicine education in emergency training is understood, no standard curriculum delivery has been proposed and little research has been done to evaluate the effectiveness of any particular model. Aim: To demonstrate a four-hour multi-modal curriculum that includes lecture based discussions and small group exercises, culminating in an interactive multidisciplinary competition that integrates the previously taught information. Methods: EMS and disaster faculty were surveyed on the previous disaster and prehospital educational day experiences to evaluate course content, level of engagement, and participation by faculty. Based on this feedback, the EMS/Disaster divisions developed a schedule for the four hour EMS and Disaster Day that incorporated vital concepts while addressing the pitfalls previously identified. Sessions included traditional lectures, question and answer sessions, small group exercises, and a tabletop competition. Structured similarly to a strategy board game, the tabletop exercise challenged residents to take into account both medical and ethical considerations during a traditional triage exercise. Results: Compared to past reviews by emergency medical faculty, residents, and medical students, there was a precipitous increase in satisfaction scores on the part of all participants. Discussion: This curriculum deviates from the conventional education model and has been successfully implemented at our 3-year residency program of 66 residents. This EMS and Disaster Day promotes active learning, resident and faculty participation, and retention of important concepts while also fostering relationships between disaster managers and the Department of Emergency Medicine.